Indonesia’s G20 Presidency 2022: Connecting Soft Power and Digital Diplomacy Practice on Instagram - Anak Agung Mia Intentilia (Universitas Diponegoro, 2022)
The purpose of this paper is to answer two research questions. The first one is how Indonesia utilizes culture as the soft power resource in G20 Presidency 2022 and the second one is the practice of Indonesia’s digital diplomacy on Instagram in G20 Presidency 2022. This research utilizes two conceptual frameworks, the concept of soft power and its cultural element, as well as the concept of public and digital diplomacy. The methodology used in this paper is a qualitative method. The primary data are gathered from Indonesia’s government statements and an official Instagram account that has been verified, @indonesia.g20, as a purposive sample. The secondary data of this article are taken from academic journals and e-books. All data used in this research are limited from December 2021 until May 2022 as part of the early phase of Indonesia’s G20 Presidency. The findings of this research are: (i) Indonesia uses the element of culture as part of promoting its soft power at the global stage through G20 by using cultural element in the G20 Presidency logo; (ii) the strategic issues regarding culture are combined with performances to showcase the variety of Indonesia’s cultural actors and communities; (iii) the practice of digital diplomacy, in terms of agenda-setting, has used three methods to spread information regarding the G20 agendas: by providing technical information, explaining substantive messages of G20 priority areas, and inviting active engagement through quizzes on G20 issues; and (iv) digital diplomacy on @indonesia.g20 Instagram account has covered the involvement of non-state actors.